CYCLOSPORIN INDUCED EFFECTS ON FOETAL KIDNEY IN ALBINO MICE - Tawakal, N; Tahir, M; Waqas, S (Journal of Ayub Medical College Abbottabad, 2010)
Background: Cyclosporin A (CsA) is an immunosuppressive agent which is used to prevent graft rejection and to treat autoimmune disorders. Its teratogenic effects remain unexplored despite its extensive use even during pregnancy. Current study was, therefore, undertaken to investigate the effects of CsA on the developing kidney. Methods: Twelve pregnant mice were divided into two groups, A and B, having six animals each. Cyclosporin was freshly prepared in normal saline daily and administered subcutaneously by a single dose of 50 mg/kg in the morning to experimental group B during pregnancy from day 0 to day 18. The control group A was given comparable volume of normal saline only. The pregnant mice were sacrificed at the end of experimental period. The foetal kidneys were dissected and fixed in 10% formalin for histological preparations. Results: The results showed that weight of the foetuses and their kidneys exposed to CsA was consistently reduced. The mean weight of the foetuses exposed to CsA was 1.34±0.08 g as compared to 1.48±0.18 g in the control group whereas the mean kidney weight from CsA treated group was 9.47±0.27 mg when compared to the control having 10.79±0.53 mg. Morphometric analysis revealed reduction in total number of glomeruli and hypertrophy of remaining glomeruli. The total number of glomeruli/mm2 in the kidneys from CsA treated group was 26.85±4.43 as compared to 41.33±3.66 from the control group and the mean diameter of glomeruli from the foetuses of groups A and B was 7.11±0.47 mm and 8.66±0.63 mm respectively; the differences between the groups A and B of the animals on all the parameters above were statistically significant (p<0.000). Conclusion: The results of the investigation indicated that CsA administration to the pregnant dams produced deleterious effects of on the developing kidney in mice. On the analogy of the results, comparable effects of CsA are expected in case of human; this, however, needs further investigations. Keywords: Cyclosporin A, nephrotoxicity